Validity and reliability of the new handball-specific complex test - Schwesig, R.; Koke, A.; Fischer, D.; Fieseler, G.; Jungermann, P.; Delank, K. S.; Hermassi, S. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to determine the intraobserver reliability (IR) of the handball-specific complex test (HBKT) and the validity of the HBKT and nonspecific tests. Thirty experienced players (25.7 ± 3.9 years) executed the HBKT twice (time interval: 2 days). Lactate, heart rate (HR), time, throwing velocity and number of errors were measured. Afterwards, players' match performances (MPs) in 30 matches were evaluated using video analysis to compare it with the test parameters. Resting HR between first half and second half (r2 = 0.26), standing long jump (r2 = 0.18), jump and reach (r2 = 0.16), and HR before second half (r2 = 0.14) were proven to be the most valid tests or parameters. The amounts of explained variance concerning the MP of all other tests/parameters were below 10%. Overall, 41% (12/29) of the parameters showed a high relative intraclass correlation coefficient (ICC > 0.75) and absolute coefficient of variation (CV = 5%) IR. Results suggest that the HBKT can be certified with an insufficient validity and a sufficient absolute (ØCV = 11.3%) and relative (ØICC = 0.67) IR. The reasons could be insufficient tests or insufficient score of MP. The current findings suggest that the coaches and scientists should recognize a lot of effort is necessary to measure MP and to develop valid tests. Additional research should aim to connect test and MP with each other. Before a coach applies a test, he should thoroughly check whether the test is valid (gold standard: MP) and reliable. The frequent and long-term test application (very common argument of the coaches in practice) is not a proof of validity.